Κατασκευαστικές λεπτομέρειες σε ξύλινη οικοδομή - Γερολέμου, Μόρφω (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Wood is a material used by human for thousands of years for house construction. Recently, technology has achieved to develop new materials, but wood continues to remain valuable of traditional applications, although the constant appearance of new wood products multiplies the possibilities of utilization. This paper, through a research on the construction details of a wooden building, reviews the construction process of the wooden building and the presentation of typical construction details that required. The paper contains four chapters. A general reference to wood and more specifically in the properties of wood, the advantages and disadvantages of wood, how is protected and maintained, and the types of wood that are available in the market. Analyzation of the supporting structure is performed which consists by the substructure, the design models of a wooden structure, the floors and the roof. It is emphasized that all the construction details and procedures that required for each job are presented including the hydraulic and the electrical installations. With the evolution of technology many things have changed about the wooden structures as required for mandatory application of the Eurocodes. This chapter presents the connection of wooden elements and the reference standards required from Eurocode 5. Finally, some conclusions are presented that arise through the review which was carried out during this dissertation.
Keywords: Wood; Wooden building; Wooden structures; Eurocode 5; Ξύλο; Ξύλινη οικοδομή; Ξύλινες κατασκευές; Ευρωκώδικας 5